Sources of auditory brainstem responses revisited: Contribution by magnetoencephalography - Parkkonen, Lauri (Hum Brain Mapp, 2009)
Auditory brainstem responses provide diagnostic value in pathologies involving the early parts of the auditory pathway. Despite that, the neural generators underlying the various components of these responses have remained unclear. Direct electrical recordings in humans are possible only in limited time periods during surgery and from small regions of the diseased brains. The evidence of the generator sites is therefore fragmented and indirect, based strongly on lesion studies and animal models. Source modeling of EEG has been limited to grand averages across multiple subjects. Here, we employed magnetoencephalography (MEG) to shed more light on the neural origins of the auditory brainstem responses (ABR) and to test whether such deep brain structures are accessible by MEG. We show that the magnetic counterparts of the electric ABRs can be measured in 30 min and that they allow localization of some of the underlying neural sources in individual subjects. Many of the electric ABR components were present in our MEG data; however, the morphologies of the magnetic and electric responses were different, indicating that the MEG signals carry information complementary to the EEG data. The locations of the neural sources corresponding to the magnetic ABR deflections ranged from the auditory nerve to the inferior colliculus. The earliest cortical responses were detectable at the latency of 13 ms. Hum Brain Mapp, 2009. © 2009 Wiley‐Liss, Inc.